How to manage your bills (collection) - Weston, Liz Pulliam; Weston, Liz Pulliam (FT Press Delivers, 2014)
Today, people struggling with debt have far fewer options: lenders are stingier, which makes it harder to avert disaster, or to recover from setbacks like foreclosure, short sales, or bankruptcy. (Meanwhile, people with good credit have more options than ever, including some of the lowest interest rates in decades.) Debtors need an up-to-date guide that can help them assess options, find help, discover opportunities, and take action that works . Liz Weston's Deal with Your Debt, Updated and Revised Edition is that guide. In this extensively updated guidebook, Weston shows which debts can actually help build wealth over time, and which are simply toxic . She presents up-to-date, real-world strategies for assessing and paying off debt, including money-saving insights on which debts to tackle first. She also offers practical guidelines for assessing how much debt is safe -- and compassionate, realistic guidance for people who've gone beyond the safety zone. In There Are No Dumb Questions About Money , nationally-renowned personal finance journalist and best-selling author Liz Weston answers your most pressing questions, helping you navigate today's more-complicated-than-ever financial world. Through real-life reader questions and clear, to-the-point answers, Weston shows how to manage your spending, figure out what you can and can't afford, and choose the smartest ways to pay off your debt. You'll discover why most investment strategies don't work, and identify better ways to save for retirement. But you'll also learn to handle the trickier, emotional side of money: how to avoid fights with your partner, deal with spendthrift children or parents, and spot con artists or lousy advisors before you get robbed. Using humor, keen insight, and time-tested financial planning principles, Weston can help you wrangle your money into shape -- and find your own path to financial freedom.